Kompresi File Advanced Audio Coding (AAC) Menggunakan Metode Lempel Ziv Oberhumer (LZO) - Enjelita Purba, Ginta (Journal of Computing and Informatics Research, 2022)
In an age of increasingly sophisticated technology such as today. The need for greater storage capacity is responsible for the emergence of various compression techniques. The more file is stored, the greater the capacity. The enormous size of file results in an inefficient memory and slow-motion process of file transfer. Getting older file storage results in more and more file piling up. As technology progresses today. And thus, a growing ability to process file is utilizing a compression method that is expected to address the problem, it will be necessary to minimize storage by using Lempel Ziv Oberhumer methods to compress Advanced Audio Coding(AAC) files to narrow the size of the beets. So by applying an Lempel Ziv Oberhumer to compression the file could reduce storage capacity optimally.